2023
DOI: 10.1007/s10212-023-00683-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between basic psychological need satisfaction and intrinsic motivation: The role of individual differences and special educational needs

Abstract: A within-person perspective with several measurement points per individual allows to analyse relations between variables within individuals. Such an approach is still scarce in research from a self-determination theory perspective. Therefore, this study measured basic psychological need satisfaction and intrinsic motivation in real-time and at several lessons with the experience sampling method. In this way, the relationship between need satisfaction and intrinsic motivation was investigated from both a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This finding is consistent with the self-determination theory, which suggests that individuals' well-being and motivation are influenced by the satisfaction of universal psychological needs (Deci & Ryan, 1985;Ryan & Deci, 2017). Previous studies have shown a correlation between basic psychological needs satisfaction and intrinsic motivation (Loopers et al, 2023;Pelikan et al, 2021). Loopers et al (2023) suggest that competence and relatedness needs have the strongest correlation with intrinsic motivation among teachers, followed by autonomy and relatedness needs with students.…”
Section: Hypothesis Testing Of Variable Influencesmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with the self-determination theory, which suggests that individuals' well-being and motivation are influenced by the satisfaction of universal psychological needs (Deci & Ryan, 1985;Ryan & Deci, 2017). Previous studies have shown a correlation between basic psychological needs satisfaction and intrinsic motivation (Loopers et al, 2023;Pelikan et al, 2021). Loopers et al (2023) suggest that competence and relatedness needs have the strongest correlation with intrinsic motivation among teachers, followed by autonomy and relatedness needs with students.…”
Section: Hypothesis Testing Of Variable Influencesmentioning
confidence: 94%
“…Previous studies have shown a correlation between basic psychological needs satisfaction and intrinsic motivation (Loopers et al, 2023;Pelikan et al, 2021). Loopers et al (2023) suggest that competence and relatedness needs have the strongest correlation with intrinsic motivation among teachers, followed by autonomy and relatedness needs with students.…”
Section: Hypothesis Testing Of Variable Influencesmentioning
confidence: 94%